IMPLEMENTASI GREEN SMART VILLAGE DI DALAM UPAYA MENINGKATKAN PEMBANGUNAN DESA (DESA BANYUANYAR KECAMATAN AMPEL KABUPATEN BOYOLALI) - Elida Suci Hermayanti; Teguh Yuwono (Journal of Politic and Government Studies, 2020)
Today, villages in Indonesia need to be developed into a smart village. According to themandate of Law No. 6 of 2014, the village has the authority to regulate village affairs through theallocation of village funds. It aims to develop the potential of the village and realize the welfare ofsociety through Village Development. One of the innovative steps in conducting Villagedevelopment can be done with the implementation of Green Smart Village concept as done by thegovernment of Banyuanyar village, Ampel subdistrict, Boyolali district. In addition to developingthe potential of the village as a form of community welfare, the program also supports the SmartCity program that has been launched by the government of Boyolali district. This research aims todetermine the implementation of Green Smart Village in Banyuanyar village and supportingfactors as well as the implementation factor of the program. Efforts to address problems andresearch objectives were conducted using the implementation theory of George Edwards III. Thestudy uses mixed methods, where data is obtained through interviews, data/archives, andquestionnaires. The results showed that the idea of Green Smart Village is an effort to explore thepotential of the village, the implementation of Green Smart Village realized through the provisionof free internet access for the community of Banyuanyar Village, the development of digital libraryfacilities, government services of IT-based village, and the development of integrated livestockand agriculture field. The result of infrastructure development has improved, but in terms of theeconomic program is still not able to reach the entire village community. Through researchconcluded that of the four indicators of the implementation theory of George Edwards III, two ofwhich have been implemented well namely the indicator of communication and disposition. Twoother indicators are the indicator of resources and bureaucracy structure still there is a shortage ofhuman resources both implementing and village community, the source of funds that are stilllacking to support the activities of Green Smart Village, in addition to the indicator bureaucraticstructure has no special management structures that run the program.Key Words: Green Smart Village, implementation, Village development